Translation of the sequence AGG-AGG yields 50% ribosomal frameshift. - Spanjaard, R A (1988)
We have inserted the sequence 5'-AAG-GAGGU-3', which is complementary to the 3' terminus of Escherichia coli 16S rRNA, in a reading frame and analyzed its effect on the accuracy and overall rate of translation in vivo. Translation over the sequence yields a 50% ribosomal frameshift if the reading phase is A-AGG-AGG-U. The other two possible frames do not give shifts. The introduction of a UAA stop codon before (UAA-AGG-AGG-U) but not after (A-AGG-AGG-UAA) the AGG codons abolishes the frameshift. The change in the reading phase occurs exclusively to the +1 direction. Efficient frameshifting is also induced by the sequence A-AGA-AGA-U. The arginine codons AGG and AGA are read by minor tRNA. Suppression of frameshifting takes place when a gene for minor tRNA(Arg) is introduced on a multicopy plasmid. We suggest that frameshifting during translation of the A-AGG-AGG-U sequence is due to the erroneous decoding of the tandem AGG codons and arises by depletion of tRNA(Arg). The complementarity of tandem AGG codons to the 3' terminus of 16S rRNA is a coincidence and apparently not related to the shift. Replacing the AGG-AGG sequence by the optimal arginine codons CGU-CGU does not increase the overall rate of translation.